1980
DOI: 10.1128/iai.27.2.682-685.1980
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid associated with pathogenicity and calcium dependency of Yersinia enterocolitica

Abstract: Studies of the virulence and plasmid properties of Yersinia enterocolitica revealed a plasmid, 42.2 ± 1.1 megadaltons in size, which is associated with the pathogenicity and calcium dependency of this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
199
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(208 citation statements)
references
References 18 publications
8
199
0
1
Order By: Relevance
“…Bacteria were grown in Tryptic soy agar (Difco Laboratories, Detroit, MI) at 25°C for 24 h. Bacterial cells were harvested, washed, and resuspended in sterile water to obtain about 109 bacteria per ml. The mice were infected as described by Gemski et al [5]. After an 18-h period of water deprivation, mice were allowed to drink ad libitum for 24 h from bacterial suspension.…”
Section: Oral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were grown in Tryptic soy agar (Difco Laboratories, Detroit, MI) at 25°C for 24 h. Bacterial cells were harvested, washed, and resuspended in sterile water to obtain about 109 bacteria per ml. The mice were infected as described by Gemski et al [5]. After an 18-h period of water deprivation, mice were allowed to drink ad libitum for 24 h from bacterial suspension.…”
Section: Oral Infectionmentioning
confidence: 99%
“…Previous reports have shown that Y. enterocolitica serotype 08 with the virulence plasmid has the ability to cause intestinal infection with persistent presence of viable yersiniae in the ileal contents, ileal tissue, and Peyer's patches [5,20]. We compared the virulent strain IP383 of serotype 09 and its plasmid-less derivative IP383p-for their abilities to survive in the Peyer's patches after oral challenge (Table 1).…”
Section: Survival Of Bacteria In the Peyer's Patchesmentioning
confidence: 99%
“…Yersinia enterocolitica is now recognized as an important cause of gastroenteritis in man [1]. We have previously reported the presence of plasmids (designated Vwa) that are associated with the virulence of Y. enterocolitica serotype 0:8 and Y. pseudotuberculosis serotype III as shown by mouse lethality tests following either oral or intraperitoneal injection [2,3]. In addition, the presence of such Vwa plasmids was associated with the temperature-dependent production of V and W antigen and expression of a calcium dependency by Y. enterocolitica when grown at 37°C [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the presence of plasmids (designated Vwa) that are associated with the virulence of Y. enterocolitica serotype 0:8 and Y. pseudotuberculosis serotype III as shown by mouse lethality tests following either oral or intraperitoneal injection [2,3]. In addition, the presence of such Vwa plasmids was associated with the temperature-dependent production of V and W antigen and expression of a calcium dependency by Y. enterocolitica when grown at 37°C [2,3]. The V and W antigens of Y. enterocolitica have been now shown to be immunologically identical to those of Y. pestis and Y. pseudotuberculosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a 40-48. 106Mr plasmid appears to be associated with virulence in Yersinia pestis, Yersinia pseudotuberculosis and Yersinia enterocolitica [1][2][3]. A variety of properties, such as the production of V and W antigens [2,4], calcium-dependent growth at 37°C [2,3], tissue invasiveness [5], and monolayer detachment [4], appear to be related to both virulence and carriage of this class of plasmid.…”
Section: Introductionmentioning
confidence: 99%